2020
DOI: 10.3389/fimmu.2020.00415
|View full text |Cite
|
Sign up to set email alerts
|

Intact B-Cell Signaling and Function With Host B-Cells 47 Years After Transplantation for X-SCID

Abstract: Introduction: Severe Combined Immunodeficiency (SCID) is a life-threatening immunodeficiency caused by several pathogenic genetic variants, and it is characterized by profound defects in T-cell numbers and immune function. First performed in the late 1960's, hematopoietic stem cell transplantation remains the standard treatment for most cases of SCID. There is a growing number of post-transplant SCID patients, and it is imperative to assess the long-term outcomes of these patients. We have reported here the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The IL2RG variant p.V152A could be hypomorphic and allow for some signaling through the IL7R. Certainly other variants of IL2RG allow for some cytokine signaling, as we recently showed for a variant that allows for IL-21 signaling [19]. In this model, however, one also needs to assert that the capability of partial IL7R signaling is sufficient to allow for genesis of B cells but not T cells, which we have no evidence for.…”
Section: Discussionmentioning
confidence: 65%
“…The IL2RG variant p.V152A could be hypomorphic and allow for some signaling through the IL7R. Certainly other variants of IL2RG allow for some cytokine signaling, as we recently showed for a variant that allows for IL-21 signaling [19]. In this model, however, one also needs to assert that the capability of partial IL7R signaling is sufficient to allow for genesis of B cells but not T cells, which we have no evidence for.…”
Section: Discussionmentioning
confidence: 65%
“…In some early studies, primary immunodeficiency constitutes the most frequent underlying diseases associated with PCP in infants [ 164 ]. We provided a comprehensive list of primary immunodeficient diseases associated with PCP ( Table 2 and Table S2 [ 86 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ,…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…The lack of B-cell functional recovery observed in SCID-X1 patients despite successful T-cell reconstitution is likely due to a failure in the signaling through IL-21 in B-cells (14) and is associated with a reduced donor B-cell engraftment particularly in unconditioned procedures (38,(45)(46)(47)(48). Nevertheless, a recent study reported an ongoing B-cell response with intact host B-cell signaling through IL-21 in a SCID-X1 patient 47 years after the HSCT, although this is most likely due to a hypomorphic gc variant (49).…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%